SOCIAL SKILLS TRAINING IN CHILDREN AT A SOCIAL ASSIS-TANCE REFERENCE CENTER - Consuêlo T. Oliveira, Núbia; Giardini Murta, Sheila; Paula Silva, Mariana (Revista Gênero e Interdisciplinaridade, 2022)
This article describes training in social skills for children in situations of social vulnerability. 13 children participated, aged 7 to 12 years, linked to the Social Assistance Reference Center (CRAS). The children participated in 11 sessions and their parents in 2 sessions, all lasting 90 minutes. GThe inclusion of social skills training in CRAS as a strategy for preventing and reducing risk factors in childhood is discussed.